Gc-hrms screening & anticancer activity of bioactive compounds from crude extracts of Colletotrichum Gloeosporioides F.SP. Pilosae - RAHAT UBAID ANSARI,; SASHIREKHA SURESHKUMAR, (International Journal of Pharma and Bio Sciences, 2019)
Phylloplane fungi are fungi growing on the surface of the leaf. Leaf and fungi grow in association with each other either symbiotically or asymbiotically. The present investigation explores the presence of potential bioactive compounds present in the leaves of Garuga pinnata and Colletotrichum gleosporoides. The fungus was screened for the presence of bioactive compounds using GC-HRMS. Further these compounds were analysed for anticancer activity against two human cancer cell lines. About 14 bioactive compounds in ethyl acetate of Garuga pinnata leaves & 18 bioactive compounds in the ethyl acetate extracts of Colletotrichum gleosporoides were detected. Colletotrichum showed anticancer activity on cancer cell lines SiHa & SCC – 40 causing 50% inhibition of cell growth of cervical & oral tissues.